Nonalbuminuric chronic kidney disease: A dominant presentation in noncommunicable disease population of rural central India - Kodgirwar, Piyush Shankarrao (J Family Med Prim Care, 2018)
BACKGROUND: India has largest number of people with diabetes mellitus (DM), and hypertension (HTN) is expected to double in next 25 years, which are common causes of chronic kidney disease (CKD). The focus for prevention of end-stage renal disease has shifted to detection of the iceberg of DM and HTN and its adequate control. Prevalence studies of CKD in India rural community are lacking. METHODOLOGY: We did community-based cross-sectional study with 3 monthly diagnostic camps in adults ≥20 years (n = 6278), from 13 villages for early detection of CKD in rural population around Sevagram in a group of noncommunicable disease (NCD) with DM, HTN, ischemic heart diseases (IHD), and stroke in year 2015–2016. RESULTS: Study achieved 87% (5440/6278) coverage for albuminuria screening. Prevalence of CKD in NCD population was 19.6% (220/1121) where 86% (181/220) were nonalbuminuric CKD. Prevalence of persistent albuminuria in the study population was 0.8% (45/5440); in NCD population (DM, HTN, IHD, and stroke), it was 2.8% (31/1121). Prevalence of CKD was 19% in HTN and 18.9% in diabetes. The prevalence of nonalbuminuric versus albuminuric CKD was 17.1% versus 1.9% (9 times) in hypertensive individuals and 11.3% versus 7.5% (1.5 times) in individuals with DM. CONCLUSION: Predominance of nonalbuminuric CKD in NCD participants raises suspicion of CKD with undetermined risk factors. Further studies are needed to find the prevalence of nonalbuminuric CKD in overall population and to find out if exposure of pesticides, chemical fertilizers over long duration play an important role in agrarian rural community.